2017
DOI: 10.18632/oncotarget.19549
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the subcellular localization of Epstein-Barr virus encoded proteins in live cells

Abstract: Epstein-Barr virus (EBV) is the pathogenic factor of numerous human tumors, yet certain of its encoded proteins have not been studied. As a first step for functional identification, we presented the construction of a library of expression constructs for most of the EBV encoded proteins and an explicit subcellular localization map of 81 proteins encoded by EBV in mammalian cells. Viral open reading frames were fused with enhanced yellow fluorescent protein (EYFP) tag in eukaryotic expression plasmid then expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 86 publications
4
37
0
Order By: Relevance
“…The number of H-Bond, Helice, Strand and Turn included in this model were 81, 7, 2, and 16, respectively. confirms again the previous report (33). However, the future study needs to be carried out to determine whether BGLF2 possess similar functions with its homologues.…”
Section: Discussionsupporting
confidence: 88%
“…The number of H-Bond, Helice, Strand and Turn included in this model were 81, 7, 2, and 16, respectively. confirms again the previous report (33). However, the future study needs to be carried out to determine whether BGLF2 possess similar functions with its homologues.…”
Section: Discussionsupporting
confidence: 88%
“…BFLF2 is a nuclear phosphoprotein of approximately 35 kDa, expressed early during viral replicative cycle, but is not detectable in extracellular virions [16]. Our recent study showed that BFLF2 localizes absolutely to the nucleus [3], which is in accordance with the subcellular localization of HSV-1 UL31 [19,20]. However, the determining mechanisms for its subcellular transport were not well understood, thus prompting us to investigate the nucleocytoplasmic transport mechanisms of BFLF2.…”
Section: Introductionmentioning
confidence: 93%
“…The BFLF2 open reading frame (ORF) was polymerase chain reaction amplified from BAC DNA of EBV B95-8 strain (174-kb BAC) [3,22], then the product was digested with EcoRI and BamHI and inserted into the green fluorescent protein variant mammalian expression vector pEYFP-N1 (Clontech, BD Biosciences, Palo Alto, CA) encoding enhanced yellow fluorescent protein (EYFP), to creat pBFLF2-EYFP. Fragments and mutants of BFLF2 were inserted into pEYFP-C1 (Clontech, BD Biosciences) to analyze the functions of the predicted NLS and NES.…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations